Longitudinal study shows no effect of supplements on cognition in elderly. Issue 12 (December 2015) - Unknown
Abstract : The second phase of a longitudinal study examining the effects of nutritional supplements on macular degeneration has found no significant beneficial or detrimental effect on cognitive function of omega‐3 fatty acids or the combination of lutein and zeaxanthin. The study population's average age of nearly 73 leaves unanswered the question of whether individuals could derive greater benefits from supplementation if it were started earlier in life. Study results were published Aug. 25, 2015, in the Journal of the American Medical Association .